New records of the genus Cortinarius for India - Sood, Shilpa; Singh, Reeti; Upadhyay, Ramesh Chandra (Mushroom Research, 2021)
During the survey of mycorrhizal mushroom, three species of Cortinarius viz. Cortinarius bulliardii,Cortinarius dionysae, and Cortinarius pseudoglaucopus were encountered. In the present study thesespecies were described morphologically and anatomically and Cortinarius dionysae and Cortinariuspseudoglaucopus are new for India.